"I can see it in your eyes": Biased Processing and Increased Arousal in Dishonest Responses. (29th December 2015) - Hochman, Guy; Glöckner, Andreas; Fiedler, Susann; Ayal, Shahar
Abstract: According to self‐maintenance theory, people notice their dishonest acts and thus experience ethical dissonance between their misconduct and their positive moral self. In this view, dishonesty is facilitated by justifications that redefine moral boundaries. By contrast, the bounded ethicality approach suggests that biased perception prevents people from becoming aware of their dishonesty. We tested the key process assumptions behind these accounts using pupillary responses and fixation data and found physiological evidence for both kinds of mechanisms. In particular, physiological arousal increased at the initial stage of cheating responses. This suggests that people are on some level aware of their wrongdoings. At the same time, however, we found attentional biases that can reduce the likelihood for detecting potentially disadvantageous information. We suggest that dishonest acts come at the internal cost of increased tension, which people aim to avoid by pre‐emptive biased processing as well as post hoc justifications. Copyright © 2015 John Wiley & Sons, Ltd.